2008
DOI: 10.1063/1.2996297
|View full text |Cite
|
Sign up to set email alerts
|

Energetics, structure, and charge distribution of reduced and oxidized n-pyrrole oligomers: A density functional approach

Abstract: Polypyrrole is a conjugated polymer prototype of conducting polymers. The energetically preferred spatial conformation of n-pyrrole oligomers (n=1-24) in both the reduced and oxidized phases is obtained and analyzed in this paper within the hybrid density functional theory. Binding energies, gap energies, radius of gyration, end-to-end distance, and vibrational frequencies are reported as functions of oligomer length. Reduced n-pyrrole are bent chains for all sizes showing a dramatic departure from planarity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
54
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(62 citation statements)
references
References 32 publications
(32 reference statements)
6
54
0
2
Order By: Relevance
“…As discussed in the introduction, several previous studies have examined the molecular and electronic structure of PPy oligomers using a range of ab initio theory [3, 810]. Earlier works were limited by computational cost and used less accurate basis sets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed in the introduction, several previous studies have examined the molecular and electronic structure of PPy oligomers using a range of ab initio theory [3, 810]. Earlier works were limited by computational cost and used less accurate basis sets.…”
Section: Resultsmentioning
confidence: 99%
“…Thus undoped oligo or polypyrrole have non-planar structures and are likely to be rather flexible. Most recently, a quantum mechanics (QM) study of the equilibrium structures of oligomers up to 24 rings in length showed that higher doping ratios produce more planar chains [10]. They also showed that explicitly including dopant ions in QM calculations with oxidized PPy chains increased the localization of positive charge near the doping sites.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrrole and pyrrole oligomers have been subjected to several investigations determining various properties including electronic structure, vibrational frequencies, ionization potential, and electron affinity and effect of doping on these properties [12][13][14]. It has been found that aromatic compounds are adsorbed on CNT surfaces through stacking interactions [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidized PPy is a polycationic conductor that synthesizes forming thin or thick films. [17][18][19][20][21][22][23][24][25][26][27][28] However, the level of these calculations is computationally intractable for studying condensed phases that are not crystalline. By reduction, the electrical conduction property is lost and the structure of the conjugated polymer chain becomes benzenoid.…”
Section: Introductionmentioning
confidence: 99%
“…27 This potential treats the Py monomers as rigid molecules with a permanent dipole moment anchored at their centers and contains interactions pertaining to intra-and interoligomer chains. 27 This potential treats the Py monomers as rigid molecules with a permanent dipole moment anchored at their centers and contains interactions pertaining to intra-and interoligomer chains.…”
Section: Introductionmentioning
confidence: 99%